2014
DOI: 10.1186/s12917-014-0184-9
|View full text |Cite
|
Sign up to set email alerts
|

The long-acting COX-2 inhibitor mavacoxib (Trocoxil™) has anti-proliferative and pro-apoptotic effects on canine cancer cell lines and cancer stem cells in vitro

Abstract: BackgroundThe NSAID mavacoxib (Trocoxcil™) is a recently described selective COX-2 inhibitor used for the management of inflammatory disease in dogs. It has a long plasma half-life, requiring less frequent dosing and supporting increased owner compliance in treating their dogs. Although the use of NSAIDs has been described in cancer treatment in dogs, there are no studies to date that have examined the utility of mavacoxib specifically.ResultsIn this study we compared the in vitro activity of a short-acting no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Caspase‐independent cell death has been previously characterized, highlighting that caspase inhibitors do not prevent cell death through autophagy, necrosis and apoptosis‐like cell death . Previous studies have noted similar results with NSAIDs in cancer cell lines, with caspase‐independent and BAX‐independent apoptosis suggested as a possible explanation . We have previously shown that increased Bcl‐2 levels after COX‐2 inhibition may be the result of a mitochondrial‐independent apoptotic pathway .…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Caspase‐independent cell death has been previously characterized, highlighting that caspase inhibitors do not prevent cell death through autophagy, necrosis and apoptosis‐like cell death . Previous studies have noted similar results with NSAIDs in cancer cell lines, with caspase‐independent and BAX‐independent apoptosis suggested as a possible explanation . We have previously shown that increased Bcl‐2 levels after COX‐2 inhibition may be the result of a mitochondrial‐independent apoptotic pathway .…”
Section: Discussionmentioning
confidence: 50%
“…The canine osteosarcoma cell lines, KTOSA5 and CSKOS (gifted from Chand Khanna [NIH]) were maintained in Dulbecco's modified Eagle's medium (DMEM) (ThermoFisher Scientific, Massachusetts). The human osteosarcoma cell line U2OS was grown in McCoys 5A modified medium (ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dissection of the mechanisms by which PGE 2 exerts these effects on HSCs has identified in vivo evidence that PGE 2 enhances the activation of Wnt, a key regulator of stem cell self-renewal, during embryogenesis by stabilising β -catenin, and that Wnt-mediated regulation of HSC development is PGE 2 -dependent [67]. Given the stem-cell-enhancing activity of PGE 2 , and that PGE 2 activates general cell survival and proliferation pathways, it is unsurprising that upregulation of COX-2 is associated with populations of CSCs isolated from several cancer types, including breast [7477], colon [78, 79], and bone cancer [13, 80]. COX-2 is coexpressed with CSC markers including CD44, CD133, Oct3/4, LGR5, SOX-2, and ALDH [75, 78, 8184].…”
Section: Cox-2 Plays a Central Role In Cancermentioning
confidence: 99%